1998
DOI: 10.1001/archotol.124.12.1325
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor and Insulinlike Growth Factor I Support the Growth of Human Septal Chondrocytes in a Serum-Free Environment

Abstract: The combination of IGF-I and bFGF in a serum-free and a serum-supplemented environment supports the growth and viability of human septal chondrocytes in short-term culture. In an SFM, the results obtained approximate those produced in a medium enhanced with 10% fetal calf serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…[25][26][27][28] Richmon et al found increased GAG accumulation during monolayer culture of human nasal septal chondrocytes with IGF-1. 29 van Osch et al reported increased GAG accumulation and type II collagen during alginate bead culture with a combination of IGF-1 and TGFb-2.…”
Section: Figmentioning
confidence: 99%
“…[25][26][27][28] Richmon et al found increased GAG accumulation during monolayer culture of human nasal septal chondrocytes with IGF-1. 29 van Osch et al reported increased GAG accumulation and type II collagen during alginate bead culture with a combination of IGF-1 and TGFb-2.…”
Section: Figmentioning
confidence: 99%
“…A number of supplementary factors working in cohort seem to be required to rescue cells from SWinduced apoptosis, because rescue was not observed with ECGS alone and because only partial rescue was observed with IGF-1 and bFGF, even at concentrations higher than would normally be used for supplementing growth media (Dunham and Koch, 1998;Saltau and McLaughlin, 1993). Addition of all CGM components, however, successfully rescued cells from undergoing SW-induced apoptosis.…”
Section: Sw-induced Ec Apoptosismentioning
confidence: 99%
“…Our laboratory has already successfully expanded human septal chondrocytes in a serum-free in vitro model. 17 As a prelude to in vitro fabrication of hyaline cartilage in a completely serum-free process, we studied the feasibility of ex vivo generation of cartilage tissue equivalents from fresh and cryogenically preserved septal chondrocytes. Because fabrication of implants for human use requires highfidelity tissue regeneration, our studies combined the use of cell-PGA scaffolding constructs for efficient cell delivery with bioreactors.…”
Section: Construct Analysismentioning
confidence: 99%